A space charge dynamics based model for lifetime evaluation of insulating polymers. (January 2020) - Huang, Meng; Zhou, Yuanxiang
Highlights: A model is proposed to give a description of lifetime in a wide electric field range. Values of fraction parameters can be easily deduced. Influence of space charge dynamics on electromechanical energy release is electric field-dependent. Lifetime-electric field curve is piecewise linear. Abstract: To explain the generally observed and applied electric field dependent lifetime of insulating polymers, a model based on space charge dynamics has been proposed. Electric field strength affects trapping and detrapping coefficients, then the electromechanical energy released by space charge dynamics is influenced, which is a direct factor of molecule scission and dielectric breakdown. Hence static and dynamic space charge breakdown occurs under low and high electric fields, respectively. The combined consideration of charge trapping and detrapping helps to extract some adjustable parameters and give a description of lifetime in a wide electric field range. The simulation results show that the lifetime-electric field curve is piecewise linear in double logarithmic coordinates, indicating that charge dynamics are responsible for electric field dependent lifetime. Charge trapping accounts for low field lifetime while charge detrapping determines high field lifetime. The model reveals that it is improper to predict lifetime at low electric fields from lifetime test at high electric fields immediately.